2023
DOI: 10.1186/s40168-023-01606-x
|View full text |Cite
|
Sign up to set email alerts
|

High-fat diet-disturbed gut microbiota-colonocyte interactions contribute to dysregulating peripheral tryptophan-kynurenine metabolism

Abstract: Background Aberrant tryptophan (Trp)-kynurenine (Kyn) metabolism has been implicated in the pathogenesis of human disease. In particular, populations with long-term western-style diets are characterized by an excess of Kyn in the plasma. Host-gut microbiota interactions are dominated by diet and are essential for maintaining host metabolic homeostasis. However, the role of western diet-disturbed gut microbiota-colonocyte interactions in Trp metabolism remains to be elucidated. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 75 publications
0
5
0
1
Order By: Relevance
“…Several studies show that KYN/TRP ratio is associated with important biomarkers of disease activity, C-reactive protein, sedimentation rate 73 , and endoscopic score 74 . Interestingly, phylum Proteobacteria -derived lipopolysaccharide (LPS) stimulated colonic immune responses upregulates the indoleamine 2,3-dioxygenase 1 (IDO1)-mediated Kyn pathway, leading to TRP depletion and KYN accumulation in the circulation 75 . AuPhos treatment reduced the level of KYN (L-Kynurenine) and its hydroxy-derivatives (3-Hydroxykynurenine) in Hu- Il10-/- mice compared to vehicle treated group ( Fig 6C ).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies show that KYN/TRP ratio is associated with important biomarkers of disease activity, C-reactive protein, sedimentation rate 73 , and endoscopic score 74 . Interestingly, phylum Proteobacteria -derived lipopolysaccharide (LPS) stimulated colonic immune responses upregulates the indoleamine 2,3-dioxygenase 1 (IDO1)-mediated Kyn pathway, leading to TRP depletion and KYN accumulation in the circulation 75 . AuPhos treatment reduced the level of KYN (L-Kynurenine) and its hydroxy-derivatives (3-Hydroxykynurenine) in Hu- Il10-/- mice compared to vehicle treated group ( Fig 6C ).…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study, Sun and his colleagues found that long-term high-fat diets disrupted the metabolism of Trp in the bloodstream in mice [51]. This disruption was characterized by a reduction in Trp levels and an increase in the activity of the KP.…”
Section: Role Of the Intestinal Flora In The Kp Metabolismmentioning
confidence: 98%
“…This disruption was characterized by a reduction in Trp levels and an increase in the activity of the KP. Notably, this aberrant Trp metabolism strongly correlated with the proliferation of the Proteobacteria phylum in the colon, so deviations in Trp metabolism can induce changes in the KP metabolism [51] as well. In this interesting research, the authors could abrogate the long-term high-fat diet shift with antibiotic treatment, but changes induced by the long-term high-fat diet could be transferred to mice with a standard diet through fecal transplantation, thus revealing the role of gut microbiota in this process.…”
Section: Role Of the Intestinal Flora In The Kp Metabolismmentioning
confidence: 99%
“…Also, changes in microbial composition are thought to play a key role in regulating the MGBA and influencing the brain and gut function ( Borre et al, 2014 ; Sun et al, 2023 ). The MGBA is a bi-directional communication network between gut microbes and central neural system.…”
Section: Introductionmentioning
confidence: 99%